2014
DOI: 10.1148/radiol.14121326
|View full text |Cite
|
Sign up to set email alerts
|

Case 210: Primary Ovarian Lymphoma

Abstract: Abdominopelvic CT scans showed solid masses involving both ovaries (Fig 1a). Both ovaries were abnormally enlarged; the right ovary measured 16 3 10 3 11 cm, and the left ovary measured 6.2 3 3.7 3 5.3 cm. Both ovaries contained low-attenuation cysts displaced toward the periphery by an infiltrating soft-tissue tumor (Fig 1b, 1c). The infiltrating mass encased the right gonadal vessels (Fig 1d) from the hilum of the ovary (Fig 2) to the retroperitoneum; however, the vessels were not occluded. These findings we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 12 publications
0
0
1
Order By: Relevance
“…2 In almost all cases, non-Hodgkin lymphoma (NHL) with diffuse B-cell type is the commonest type, followed by Burkitt's lymphoma. Chein JC et al 3 in their study on primary ovarian lymphoma reported CA-125 level of 1366 U/ml 3 & mean level of 1111U /ml 3 but in our case, it is in lower side 839 U/ml 3 . This is a rare case with non-specific findings, hence Radiologists should be aware of this diagnosis.…”
Section: Discussioncontrasting
confidence: 60%
“…2 In almost all cases, non-Hodgkin lymphoma (NHL) with diffuse B-cell type is the commonest type, followed by Burkitt's lymphoma. Chein JC et al 3 in their study on primary ovarian lymphoma reported CA-125 level of 1366 U/ml 3 & mean level of 1111U /ml 3 but in our case, it is in lower side 839 U/ml 3 . This is a rare case with non-specific findings, hence Radiologists should be aware of this diagnosis.…”
Section: Discussioncontrasting
confidence: 60%